The Wisdom of Jesus Sirach in the Sermon on the Mount (Matthew 5–7) - van Rooy, Herculaas F. (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
The use of the Old Testament in the New Testament has been the subject of intensive research. Writings other than the books of the Old Testament have also received attention, such as the Wisdom of Jesus Sirach. This study focuses on several texts in the Gospel of Matthew that have been linked to Sirach in the past, studying intertextual relations between the different versions in different languages by using a comparative textual critical approach. The relevant texts from Matthew 5–7 and Sirach were listed, followed by a brief description of the textual history of Sirach in Hebrew, Greek, Latin and Syriac. The texts of Matthew in the Greek New Testament were analysed and compared with their translations in Latin and Syriac. The texts in Sirach that Matthew may have alluded to were studied, with attention to the original Hebrew and the translations of Sirach. The two translations of Matthew usually follow the Greek closely. In Matthew 6:12, the issue of forgiveness was a common one in Jewish circles. Granting forgiveness and receiving it are linked. This is also the case in Sirach 28:2. The Latin version of Sirach differs only stylistically from the Greek. The Syriac does not mention the neighbour, but has a general statement directed at a person’s heart. In Matthew 6:13, the reference to temptation or trial, and to evil or the evil one, was discussed. The Syriac version of Sirach 23:1 probably followed a different Hebrew Vorlage than the Greek version. Sirach 33:1 is the only text where the Hebrew is extant. The Greek follows the Hebrew closely, as does the Syriac. The Latin differs regarding the plural of evil, and it makes the Lord the subject of deliverance. This points to a deliberate revision in the Latin to make the mention of the Lord explicit. In Matthew 6:20, the only important issue is the translation of erugo in Latin. It is the word for the rust on copper. The Syriac translated the word with ‘worm’. The idea of treasures links Sirach 29:11 to Matthew 20. The Latin follows the Greek closely. The reference to almsgiving and love in Sirach could be the result of a different Vorlage. Contribution: This study throws new light on the intertextual relation between Sirach and Matthew, dealing with the different old translations of the two texts.